2007
DOI: 10.1093/ajcn/86.2.397
|View full text |Cite
|
Sign up to set email alerts
|

Infectious etiology modifies the treatment effect of zinc in severe pneumonia

Abstract: Our results suggest that the treatment effect of zinc for severe pediatric pneumonia may be modified by bacterial infection. Further studies are required to develop appropriate recommendations for the use of zinc in the treatment of severe pneumonia. This trial was registered at clinicaltrials.gov as NCT00198666.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 44 publications
1
34
2
3
Order By: Relevance
“…Studies on the effect of zinc supplementation on pneumonia have not reported the prevalence of HIV in the patients studied [10,20]. None the less, the prevalence of HIV in children in our study was high.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Studies on the effect of zinc supplementation on pneumonia have not reported the prevalence of HIV in the patients studied [10,20]. None the less, the prevalence of HIV in children in our study was high.…”
Section: Discussioncontrasting
confidence: 79%
“…We did not find a similar study with which to compare our results. In a related study, Cole and Bose [20] used a CRP of > 40 mg/L as a proxy for bacterial pneumonia. They found that zinc therapy for children with severe pneumonia was associated with prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…A total of thirteen studies remained after screening titles/abstracts. Among the thirteen studies, four were excluded, of which one (23) was an advanced abstract of an included study, two (24,25) focused on children with severe acute lower respiratory tract infection (LRTI) but not severe pneumonia and one (26) used the same data from the included trial. Finally, nine RCT (9)(10)(11)(12)(13)(14)(15)(16)(17) were included.…”
mentioning
confidence: 99%
“…A similar study in India (2007) on 299 children aged 2–23 months and hospitalized due to severe pneumonia showed that, compared to the comparison group, disease symptoms were improved faster and the duration of hospitalization decreased significantly in the zinc-receiving patients [17]. …”
Section: Discussionmentioning
confidence: 99%